Living Law Fatwa of Dsn-Mui Discrepancy Implementation of Regarding Consumer Protection in Islamic Banks at NTB - Rahmawati; Makhrus; Abdul Mujib; Ridwan (CV. Creative Tugu Pena, 2026)
This article examines the implementation gap of the murābaḥah bil-wakālah contract at NTB Syariah Bank from the perspective of the DSN-MUI fatwa as living law, and how that gap produces legal uncertainty and weakens consumer protection. Positioned within a normative–empirical legal research design, this study applies conceptual analysis on legal certainty theory (Hart–Rawls), doctrinal analysis of DSN MUI fatwas, and empirical verification of bank practices through financial reports and supporting field findings. The study finds that Bank NTB Syariah performs the wakālah and murābaḥah contracts simultaneously in one administrative session, so that the bank has no real ownership over the goods (qabd al-ḥaqīqī) before the murābaḥah sale occurs. This makes the contract substantively resemble a fixed-margin loan rather than a sharia sale, creating sharia defect (fasid), shifting risks to consumers, and undermining the maqāṣid values of justice and asset protection. The article contributes theoretically by reaffirming fatwa DSN-MUI as a source of living law requiring institutional internalization, and practically by offering governance-based recommendations (DPS independency, ownership-based compliance audit, and contractual literacy